Server + Certification Bible (Hardcover) (photocopy) - Kay Trevor (Hungry Minds, 2001)
Lots of publishers rushed their books about the CompTIA Server+ certification to market. After all, it's a new certification and certification books tend to sell well. Trevor Kay and the team at Hungry Minds have taken care to put together a high-quality book. It'll get you up to speed on everything you'll need to understand before you can pass CompTIA's Server Hardware exam (SK0-001), and it's sufficiently detailed to serve as a reference as you put your certification to use on the job. Kay's approach to his subject is to use CompTIA's published outline of test coverage as his organizational guide, then elaborate on each of its points with lots of prose and a handful of illustrations.